Spleen size in chronic renal failure. Issue 6456 (24th November 1984) - Platts, M M; Anastassiades, E; Sheriff, S; Smith, S; Bartolo, D C
Abstract : To investigate the cause of clinically detectable splenomegaly, which is common in patients receiving regular haemodialysis, splenic volume was assessed by isotopic scanning using intravenously injected technetium-99m microspheres in 34 controls and 149 patients with chronic renal failure. Of the patients, 16 had never received dialysis, 10 were undergoing continuous peritoneal dialysis, 94 were undergoing regular haemodialysis, and 29 had undergone successful renal transplantation more than nine months previously. Mean splenic volume was increased only in the patients who were receiving haemodialysis. Splenic enlargement was probably not due to iron overload as it occurred in all patients who had received haemodialysis, 14 of whom had not received intravenous iron. No patient had had hepatitis. Splenic enlargement was probably related to the process of haemodialysis itself and may have been due either to red cell damage produced by haemodialysis or to an immunological reaction induced by a component of haemodialysis, possibly ethylene oxide.